2019
DOI: 10.1002/aur.2062
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic interactions in children exhibiting the broader autism phenotype: Is the broader autism phenotype distinguishable from typical development?

Abstract: In families raising a child with an autism spectrum disorder (ASD), infant siblings are at elevated risk for ASD and other developmental concerns, including elements of the broader autism phenotype (BAP). Typically, the BAP is indexed using standardized developmental assessments; however, these measures do not capture a number of social difficulties commonly associated with the BAP. The present study aims to expand our developmental understanding of the BAP by comparing children exhibiting the BAP to their typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Other studies have also noted fewer/lower prosocial behavior in children classified as non-TD (sometimes referred to, or further classified as exhibiting the broader autism phenotype; BAP). Examples include lower frequencies of information seeking during a social task [Cornew, Dobkins, Akshoomoff, McCleery, & Carver, 2012], less infant responsiveness during play [Kellerman et al, 2019], and descriptive reports of fewer joint attention bids [Sullivan et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have also noted fewer/lower prosocial behavior in children classified as non-TD (sometimes referred to, or further classified as exhibiting the broader autism phenotype; BAP). Examples include lower frequencies of information seeking during a social task [Cornew, Dobkins, Akshoomoff, McCleery, & Carver, 2012], less infant responsiveness during play [Kellerman et al, 2019], and descriptive reports of fewer joint attention bids [Sullivan et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gangi et al [2018] reported infants who developed ASD engaged in less gaze to face behaviors during play at 12 months of age. Similarly, Kellerman et al [2019] documented subclinical dyadic features of ASD evident during play by 15 months of age (i.e., lower infant and maternal responsiveness; lower joint engagement). However, several studies have demonstrated that parents of children with ASD are comparable interactive partners, when compared to parents of children with typical development and those with other developmental concerns [Kasari, Sigman, Mundy, & Yirmiya, 1988; Schwichtenberg et al, 2019; Siller & Sigman, 2002].…”
Section: Developmental Progress/outcome Comparisonsmentioning
confidence: 94%
See 2 more Smart Citations
“…Diagnosis is common nowadays by 18-24 months of age Submitted for review: Oct. 9, 2020 (Zwaigenbaum et al, 2015). Symptoms in early infancy include reduced or absent dyadic interaction, social responsiveness, and joint attention (Kellerman et al, 2019;Mundy, 2017;Ozonoff et al, 2010), and there is some evidence suggesting prelinguistic vocal developmental anomalies (e.g., Sheinkopf et al (2012)). Two studies previously analyzed canonical babbling ratios (CBRs) in infants with ASD.…”
Section: Canonical Babbling Development In Typical Development and Aumentioning
confidence: 99%